One-minium-only basic-set trellis min-max decoder architecture for nonbinary LDPC code - Dinh, The Cuong; Pham Thi, Huyen; Dao Tuan, Hung; Pham Xuan, Nghia (Journal of Computer Science and Cybernetics, 2021)
Nonbinary low-density-parity-check (NB-LDPC) code outperforms their binary counterpart in terms of error-correcting performance and error-floor property when the code length is moderate. However, the drawback of NB-LDPC decoders is high complexity and the complexity increases considerably when increasing the Galois-field order. In this paper, an One-Minimum-Only basic-set trellis min-max (OMO-BS-TMM) algorithm and the corresponding decoder architecture are proposed for NBLDPC codes to greatly reduce the complexity of the check node unit (CNU) as well as the whole decoder. In the proposed OMO-BS-TMM algorithm, only the first minimum values are used for generating the check node messages instead of using both the first and second minimum values, and the number of messages exchanged between the check node and the variable node is reduced in comparison with the previous works. Layered decoder architectures based on the proposed algorithm were implemented for the (837, 726) NB-LDPC code over GF(32) using 90-nm CMOS technology. The implementation results showed that the OMO-BS-TMM algorithm achieves the almost similar error-correcting performance, and a reduction of the complexity by 31.8% and 20.5% for the whole decoder, compared to previous works. Moreover, the proposed decoder achieves a higher throughput at 1.4 Gbps, compared with the other state-of-the-art NBLDPC decoders.